Enhanced long term microcircuit plasticity in the valproic acid animal model of autism - Silva, Guilherme T.; Le Bé, Jean-Vincent; Riachi, Imad; Rinaldi, Tania; Markram, Kamila; Markram, Henry (Frontiers in Synaptic Neuroscience, 2009)
A single intra-peritoneal injection of valproic acid (VPA) on embryonic day (ED) 11.5 to pregnant rats has been shown to produce severe autistic-like symptoms in the offspring. Previous studies showed that the microcircuitry is hyperreactive due to hyperconnectivity of glutamatergic synapses and hyperplastic due to over-expression of NMDA receptors. These changes were restricted to the dimensions of a mini-column (<50μm). In the present study, we explored whether Long Term Microcircuit Plasticity (LTMP) was altered in this animal model. We performed multi-neuron patch-clamp recordings on clusters of layer V pyramidal cells in somatosensory cortex brain slices (PN 12-15), mapped the connectivity and characterized the synaptic properties for connected neurons. Pipettes were then withdrawn and the slice was perfused with 100μM sodium glutamate in artificial cerebrospinal fluid in the recording chamber for 12 h. When we re-patched the same cluster of neurons, we found enhanced LTMP only at inter-somatic distances beyond minicolumnar dimensions. These data suggest that hyperconnectivity is already near its peak within the dimensions of the minicolumn in the treated animals and that LTMP, which is normally restricted to within a minicolumn, spills over to drive hyperconnectivity across the dimensions of a minicolumn. This study provides further evidence to support the notion that the neocortex is highly plastic in response to new experiences in this animal model of autism.